2001
DOI: 10.1126/science.1061620
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Obesity- and Diet-Induced Insulin Resistance with Salicylates or Targeted Disruption of Ikkβ

Abstract: We show that high doses of salicylates reverse hyperglycemia, hyperinsulinemia, and dyslipidemia in obese rodents by sensitizing insulin signaling. Activation or overexpression of the IkappaB kinase beta (IKKbeta) attenuated insulin signaling in cultured cells, whereas IKKbeta inhibition reversed insulin resistance. Thus, IKKbeta, rather than the cyclooxygenases, appears to be the relevant molecular target. Heterozygous deletion (Ikkbeta+/-) protected against the development of insulin resistance during high-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
1,293
6
34

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,739 publications
(1,408 citation statements)
references
References 26 publications
47
1,293
6
34
Order By: Relevance
“…JNK deficiency has been reported to protect mice from insulin resistance, fatty liver and diabetes 86 , and inhibition of JNK is considered to be a promising therapeutic avenue [87][88][89] . Similarly, mouse models harbouring null mutations in IKK have validated that this kinase impacts insulin signalling, and inhibition of IKK by high-dose salicylates improves insulin action in experimental models and humans 90 .…”
Section: Therapeutic Opportunitiesmentioning
confidence: 96%
See 1 more Smart Citation
“…JNK deficiency has been reported to protect mice from insulin resistance, fatty liver and diabetes 86 , and inhibition of JNK is considered to be a promising therapeutic avenue [87][88][89] . Similarly, mouse models harbouring null mutations in IKK have validated that this kinase impacts insulin signalling, and inhibition of IKK by high-dose salicylates improves insulin action in experimental models and humans 90 .…”
Section: Therapeutic Opportunitiesmentioning
confidence: 96%
“…Mice that are heterozygous for a loss-of-function mutation in IKK are partly protected from obesityinduced insulin resistance, and inhibition of IKK by highdose salicylates improves insulin action in experimental models and humans 90 .…”
Section: Nature Reviews | Molecular Cell Biologymentioning
confidence: 99%
“…by improving glycaemic control through inhibition of NF-κB activity [72,73]. Salsalate, prodrug of salicylate, which unlike aspirin and sodium salicylate does not lead to bleeding risk, can improve insulin sensitivity and glucose control in prediabetic and T2DM patients with a good safety profile [74,75].…”
Section: Salicylate and Salsalatementioning
confidence: 99%
“…However, at higher concentrations, aspirin has also been shown to block NF-kB activity by directly binding to and inhibiting the kinase activity of IKKb by reducing its ability to bind ATP (Yin et al, 1998); more recently, aspirin has also been reported to inhibit proteasome activity and consequently to interfere with degradation of IkB (Dikshit et al, 2006). As such, high-dose aspirin therapy may have applications to diseases where NF-kB activity is involved, including cancer (McCarty and Block, 2006), diabetes (Yuan et al, 2001) and heart disease (Li and Fang, 2004).…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%